Presence and phenotype of dendritic cells in uveal melanoma. Issue 7 (8th March 2007) - Polak, Marta E; Borthwick, Nicola J; Johnson, Penny; Hungerford, John L; Higgins, Bernie; Di Palma, Silvana; Jager, Martine J; Cree, Ian A
Abstract : Background: Uveal melanoma arises in an immune-privileged site and can itself add to the immunosuppressive environment. Previous studies on cutaneous melanoma have shown the presence of tolerogenic dendritic cells (DCs), which could play an important role in the progression of the tumour. Aim: To examine the presence and functional status of DCs in a small series of uveal melanomas. Methods: 10 cases of uveal melanoma were examined for the expression of FXIIIa, CD68, human leucocyte antigen (HLA)-DR, CD40, CD83, transforming growth factor βR1 and indolamine 2, 3 dioxygenase by immunohistochemical analysis on sections embedded in paraffin wax. Results: CD68-positive macrophages were present in all of the tumours and were evenly distributed throughout. DCs expressing FXIIIa-positive were seen in 7 cases, and were often found concentrated in foci within the tumour mass. These cells were dendritic and expressed high levels of HLA-DR. The DCs did not express the maturation markers CD83 or CD40. In one case, concentration of DCs around the area of tumour necrosis was observed, and some of these cells expressed CD83. Conclusion: Numerous tolerising antigen-presenting cells may play a role in melanoma-related immunosuppression in the eye, although activation of DCs may be associated with tumour necrosis.